Figures that speak - deTar, Matthew. (Syracuse)
xiii, 296 sayfa
Keywords: “If the surface of Turkish politics has changed dramatically over the decades, the vocabulary for sorting these changes remains constant: Europe, Islam, minorities, the military, the founding father (Atatürk). This familiar vocabulary functions as more than a set of descriptors of institutions, phenomena, or issues to debate in public. These five primary “figures“ emerge from national identity, public discourse, and scholarship about Turkey to represent Turkish history and political authority while also shaping history and political authority. These figures unify disparate phenomena into governable categories and index historical relations of power that define Turkish politics. As these concepts circulate, they operate as a shorthand for complex networks and histories of authority, producing and limiting ways of knowing Turkish modernity, democracy, and political culture. These figures not only are spoken and discussed in public, but they also produce the context into which they are projected, in a sense speaking on their own. In Figures That Speak, deTar explores the diverse mobilization and production of history and power in the primary figures that circulate in discourse about Turkey.” --